Social programmes and job promotion for the BRICS youth - Pedro Lara de Arruda; Ashleigh Kate Slingsby (International Policy Centre for Inclusive Growth (IPC-IG), 2014)
Youth as a concept engenders a multiplicity of definitions. This multiplicity and the contextspecific nature of the term are recognised internationally. Therefore, in this paper we begin by exploring the diverse definitions of youth among prominent international organisations and the BRICS nations (Brazil, Russian Federation, India, China and South Africa). The paper then provides insight into the re-politicisation of the youth category in light of the 2008 financial crisis and the post-2015 sustainable development agenda, which have prompted an increasing focus on the creation of decent and productive employment for youth.
Keywords: 330; Social Programmes; Job Promotion; BRICS; Youth